Preoperative Retinal Detachment Variables Causing Macular Detachment - Nishimura S; Okuda T; Higashide T; Sugiyama K (Clinical Ophthalmology)
Shunsuke Nishimura, Tetsuhiko Okuda, Tomomi Higashide, Kazuhisa Sugiyama Department of Ophthalmology, Kanazawa University Graduate School of Medical Science, Kanazawa, JapanCorrespondence: Tetsuhiko Okuda, Department of Ophthalmology, Kanazawa University Graduate School of Medical Science, 13-1 Takara-machi, Kanazawa, Ishikawa Prefecture, 920-8641, Japan, Tel +81-76-265-2403, Fax +81-76-222-9660, Email okuda@med.kanazawa-u.ac.jpPurpose: The factors that contribute to the progression of macular involvement in RRD have not been extensively investigated. The purpose of this study is to evaluate the association between the preoperative characteristics and macular status of the eyes with rhegmatogenous retinal detachment (RRD).Methods: This is a retrospective cohort study. All patients with RRDs who underwent initial pars plana vitrectomy or scleral buckling were included. Patients with RRD and macular hole retinal detachment, traumatic RD, proliferative diabetic retinopathy, proliferative vitreoretinopathy grade C or higher, diabetic retinopathy, or retinal vein occlusion were excluded. High myopia was defined as an axial length > of 26.5 mm.Results: A total of 1026 eyes of 1026 patients (mean, 55.4± 15.5 years) were included. There was a significant difference in the male (68.4%) to female (31.6%) ratio (the chi-squared test: P < 0.001). A total of 351 patients (34.2%) had high myopia. The 50– 59 years age group had the highest number of eyes with high myopia. The proportion of highly myopic eyes in the 40– 49 years group was the highest. Multiple logistic regression analysis indicated that prior cataract extraction and shorter axial length (≤ 24.5 mm) were significantly associated with macula-off RRD (P = 0.018, P = 0.043, respectively). Superior and temporal retinal breaks significantly increased and superior nasal retinal breaks significantly decreased the odds ratio of macular detachment (P = 0.018, P < 0.001, and P < 0.001, respectively).Conclusion: Previous cataract extraction, shorter axial length, and superior and temporal retinal breaks are important risk factors for macular detachment.Keywords: axial length, high myopia, macular detachment, rhegmatogenous retinal detachment, scleral buckling, vitrectomy